Metal oxides as transport layer for perovskite solar cells - Affonço, Lucas Jorge [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
Nowadays, perovskite solar cells draw great interest in the energy harvest field mainly due to the rapid increase in efficiency. Nevertheless, challenges like the stability improvement and the scalability of the layers must be surpassed. Although the perovskite layer is the center of the device, this layer alone could not reach such high performance. Transport layers are necessary and offer great aid for charge extraction, and device performance, unveiling the importance of those layers and the materials used, being those layers the focus of this work. Firstly, the niobium pentoxide deposition (electron transport layer) by slot die coating was investigated. The niobium pentoxide was presented as a viable alternative to the traditional titanium oxide, mainly due to a positive influence on the stability that might be seen through a reduction in the hysteresis. The slot die coating is an attractive solution-based deposition technique, as it allows the coating of a wide diversity of materials with high throughput, which can be favorable for large-scale production. For this goal, varied parameters were examined for the deposition process. Secondly, the usage of potassium chloride salt to mitigate the hysteresis effects between the transport layer and the perovskite was investigated, comparing its application as an additive in the perovskite precursor solution or as a passivation layer, in devices with tin oxide as transport layer. The layers were analyzed by microscopy, and the influence of the materials on the device performance was assessed using the J-V curves. Considering the slot die coating of the niobium pentoxide, the layers were successfully obtained, and the best devices reached about 12 % efficiency. Although the obtained efficiency is still low compared to the present high-performance devices, obtained through other depositions techniques less scalable and more expensive, so far, no report on the slot die coating of the niobium pentoxide for perovskite solar cells was found, For the passivation, its utilization resulted in negligible hysteresis effects. Thus, either as a layer or additive, the performances were similar. However, the outcomes indicate that the usage as an additive might be a handicap for the perovskite being more favorable to use as a passivation layer.

Atualmente as células solares de perovskitas atraem grande interesse no campo de energias renováveis, principalmente devido ao rápido aumento de eficiência alcançada por esses dispositivos. Entretanto, para alcançarem o mercado, desafio associados a estabilidade e produção em larga escala precisam ser superados. Nessas células, apesar da camada de perovskita ser crucial, ela sozinha possivelmente não alcançaria o destaque que possui, sendo sua combinação com outras camadas de grande importância. As camadas transportadoras, auxiliam na extração de cargas, e os materiais que as compõe se mostram fatores fundamentais para que os dispositivos alcancem resultados expressivos, sendo o foco deste trabalho nas camadas seletivas. Primeiramente, foi investigado a deposição do pentóxido de nióbio (camada transportadora de elétrons) por slot die coating. Este material se mostrou uma boa alternativa a tradicional utilização do dióxido de titânio. Além disso, a deposição por slot die coating é vantajosa por sua possibilidade de depositar camadas de diferentes materiais por meio de soluções e em grandes áreas. Para tal objetivo, diferentes parâmetros de deposição foram testados. As células solares de perovskita, foram construídas com êxito. Além disso, também foi investigado o impacto de estratégias de passivação entre a camada seletiva de elétrons de óxido de estanho e a perovskita. Utilizou-se cloreto de potássio, tanto como camada passivadora quanto aditivo na solução de perovskita. Em ambos os casos, as camadas foram avaliadas por meio de técnicas de microscopia e a performance do dispositivo pelas curvas J-V. Considerando os dispositivos com base no pentóxido de nióbio por slot die coating, a eficiência alcançada na melhor células foi de aproximadamente 12 %. Apesar do valor estar abaixo do observado dos dispositivos presentes na literatura que beiram as mais altas eficiências, em geral estes utilizam outras técnicas de deposição, menos escaláveis e mais caras, sendo a obtenção do mesmo por slot die coating ainda não reportada. Quanto ao efeito da utilização do cloreto de potássio, houve o quase desaparecimento da histerese. A performance geral foi bem similar independendo do método de incorporação. Apesar disso, observou-se que a incorporação como aditivo pode ser prejudicial para camada de perovskita, sendo assim mais vantajoso a aplicação como camada passivadora ou ressaltando a necessidade de encontrar outra forma de incorporar na solução.
Keywords: Transport layers; Deposition methods; Perovskite solar cell; Photovoltaic devices; Metal Oxides; Camadas transportadoras; Métodos de deposição; Células solares de perovskita; Dispositivos fotovoltaico; Óxidos metálicos